Effects of Learners' Attitude, Gender and School Type On English Language Performance: A Case Study of Thika West District - Njiiri, Joyce Muthoni (My University, 2012)
Education is the key to unlocking human potential. The acquisition of communication skills and language enables people to share their ideas and knowledge effectively. Studies done in Kenya have observed that very few secondary school leavers are effectively able to speak, read and write in English language. The purpose of this study was to investigate the attitude the learners have toward English language, the effect of attitude, gender and school type on English language performance. The motivation for the study was the continued poor performance in K.CS.E English language paper. Two theories were used in the study, the tri component theory by Breckler(1964) and Smith, (19470) and inter language theory by Selinker (1972) . The study targeted students from public day secondary schools in Thika West District. Forty students from four public day schools were randomly selected. A Five point Likert Scale questionnaire was used to find out the kind of attitude students have towards English language. An English language test was constructed and used to determine the students' performance in English language.The data was sorted and organized by use of Statistical Package for Social Sciences (SPSS) and R Statistical Software was used to analyze data. Specifically, the study focused on differences in leamer's performance in English language in relation to the following variables: Attitude towards English language: Positive and negative attitudes, gender of the learner: Boys and Girls. School type: Mixed and single schools. This was followed by a comprehensive presentation of the analyzed data where description, tables, pie charts and bar graphs were used. The performance was statistically significant predictor at 95% confidence level of one's attitude towards English language. This was so because its p-value=O.OOl which is less than the critical value(0.05%) of the study. Therefore the study concludes that the English language performance can better be explained by the attitude the Iearner-has towards English language. Learners with positive attitude towards English language had significantly better performance than learners with negative attitude. However, gender and school type were non-significant factors in determining the performance level in English language.